2006
DOI: 10.1197/j.aem.2005.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Age Effect on Efficacy and Side Effects of Two Sedation and Analgesia Protocols on Patients Going through Cardioversion: A Randomized Clinical Trial

Abstract: Background: Cardioversion (CV), a painful procedure, requires sedation and analgesia. Although several sedation agents currently are in use for CV, data on age-specific efficacy and side effects of midazolam and propofol have been limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…All but one trial reported withdrawals from the study. [10][11][12] However, the one that did not had no losses to followup. 6 Two trials reported a method for allocation concealment, but neither described the method in sufficient detail to ensure adequate concealment.…”
Section: 12mentioning
confidence: 99%
See 4 more Smart Citations
“…All but one trial reported withdrawals from the study. [10][11][12] However, the one that did not had no losses to followup. 6 Two trials reported a method for allocation concealment, but neither described the method in sufficient detail to ensure adequate concealment.…”
Section: 12mentioning
confidence: 99%
“…We found 4 RCTs that reported head-to-head comparisons of midazolam and propofol in the ED setting that could be used for the analysis of AEs and clinical effectiveness. 6,[10][11][12] We found 9 additional RCTs that did not report direct comparisons between the study drugs, but in which either midazolam or propofol had been studied and could be included in the analysis of AEs. 2,5,21,22,[29][30][31][32][33][34] An additional 15 observational studies met inclusion criteria for the analysis of AEs.…”
Section: Trial Flowmentioning
confidence: 99%
See 3 more Smart Citations